2022
DOI: 10.1186/s12889-022-13220-x
|View full text |Cite
|
Sign up to set email alerts
|

Child marriage among displaced populations – a 2019 study in Kurdistan Region of Iraq

Abstract: Background Many of the factors that increase risk of child marriage are common among refugees and internally displaced persons (IDPs). We sought to address the gaps in knowledge surrounding child marriage in displaced and host populations in the Kurdistan Region of Iraq (KRI). Methods A multistage cluster sample design was employed collecting data of KRI host communities, Iraqi IDPs, and Syrian refugees. Interviews were conducted in eligible househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…28 Many of the factors that increase the risk of child marriage are common among refugees and internally displaced persons (IDPs), especially with the last period that Iraq pass through. 29 Besides, lack of awareness and disseminated old cultural norms occupy the large base for this unhealthy practice. Nearly 3.2 school-age children in Iraq are not attending school right now.…”
Section: Discussionmentioning
confidence: 99%
“…28 Many of the factors that increase the risk of child marriage are common among refugees and internally displaced persons (IDPs), especially with the last period that Iraq pass through. 29 Besides, lack of awareness and disseminated old cultural norms occupy the large base for this unhealthy practice. Nearly 3.2 school-age children in Iraq are not attending school right now.…”
Section: Discussionmentioning
confidence: 99%
“…In Iraq, the sample was stratified into three governorates and three populations—Iraqi Kurdish host communities, Iraqi IDPs and Syrian refugees, and clusters were selected in each governorate in both camp and non-camp settings with probability proportional to size. A detailed overview of study designs implemented in each setting are described elsewhere and compiled in online supplemental file 1 for ease of reference 14–18…”
Section: Methodsmentioning
confidence: 99%
“…Among 1290 studies screened by abstracts, 32 met the eligibility criteria; 15 were qualitative studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], 10 were quantitative [6,[37][38][39][40][41][42][43][44][45] and seven were mixed-methods studies [46][47][48][49][50][51][52]. The PRISMA flowchart of included studies is shown in Fig.…”
Section: Overview Of the Studiesmentioning
confidence: 99%
“…More than 50% [6, 9, 22-24, 26, 27, 29, 31-39, 41-44, 46, 49-52], 12 studies were published between 2017 and 2020 [21,25,26,28,32,35,36,38,39,[38][39][40][41][42][43][44][45][46][47], one was published in 2013 [30] and two in 2010 [44,48].…”
Section: Overview Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation